Seni Kreatif Dengan Penggunaan Medium Sisa Dalam Era Norma Baharu - Abdul Karim, Khairi Asyraf (Idealogy Journal, 2021)
Creativity involves thinking skills and thinking that conveys ideas, while critical thinking is thinking that assesses ideas. Creative thinking terminology also carries the meaning of thinking outside the box. The current scenario does not limit us to work, but rather become more creative in thinking of an idea. The creative idea in this artwork arose when a situation asked us to always stay at home, and barred us from going out looking for the material. The uniqueness in its process is the use of materials that replace canvas, acrylic or watercolor, and drawing tools. This is due to the difficulty in obtaining art supply sources due to the Movement Control Order (MCO/PKP) which is still in force. Referring to the scenario, why don't we look around to get an idea? What is the impact if we use existing materials around to be used as a medium? Have we ever considered taking such action when faced with this situation? Isn't that called creativity? Could this be what the New Norm means? This artwork has a back to the basic concept. When the new norm takes place, it is like a baby who needs to learn the norms of life. The abstract paintings created feature basic shapes such as squares and oval that we often see everywhere in our day. It describes the basic concepts as we begin to learn to draw. This is very much related to the new norm that we need to get used to and start from the basics. It’s not just about art, it’s about creativity. Keywords Creative, Creativity, Waste Materials, Recycling, New Norms